The Simplified Geneva Score and the Utilization of the D-Dimer and Computerized Tomography for Assessing Pulmonary Embolism - Park, John H; Spresser, Cole R; Valdivia, Jorge A; Khadavi, Michael J; Das, Saikat; Ellerbeck, Edward F; Cox, Glendon G (Kansas Journal of Medicine, 2011)
Background. Pulmonary embolism (PE) is clinically suspected in many patients who complain of shortness of breath or chest pain due to its nonspecific nature. The prevalence of PE, however, is low in this population. To assist physicians in diagnostic decision making, several clinical decision rules (CDR) have been developed. The appropriate use of these CDRs has been proven to decrease the need for expensive, time consuming, and invasive diagnostic imaging procedures. In this study, the appropriateness of D-dimer and CT usage was investigated to rule out pulmonary emboli based on the simplified Geneva score. Methods. A retrospective review was performed on 74 patients with a CT scan ordered through a pulmonary embolism (PE) protocol. Using clinical data, the patients were stratified into “unlikely” and “likely” groups for the presence of PE based on the simplification of the revised Geneva score. Scores of 0-2 were graded as “unlikely” and scores of 3 or greater were “likely.” Results. There were 45/74 (60.8%) patients in the “unlikely” group. Of these, 14/45 (31.1%) received a D-dimer; eight were normal and six elevated. Only one patient in the elevated group had evidence of a PE. Of the remaining 31(39.2%) patients in the “unlikely” group that did not receive a D-dimer, only one had a PE. The “likely” group consisted of 29 (39.2%) patients of whom six received a D-dimer. Three patients had a normal D-dimer and three had an elevated level. Neither of these two groups had a PE. Of the remaining 23 (60.8%) in the “likely” group who did not receive a D-dimer, six had a PE. Conclusions. Diagnosing pulmonary emboli using D-dimer levels and CT scans may be aided by clinical decision rules such as the simplified Geneva system. This process may lead to more effective use of medical resources.